Digital Spatial Profiling Reveals Functional Shift of Enterochromaffin Cell in Patients With Ulcerative Colitis - Lyu, Dongping; Kou, Guanjun; Li, Shiyang; Li, Lixiang; Li, Bing; Zhou, Ruchen; Yang, Xiaoxiao; Tian, Wenyu; Li, Yanqing; Zuo, Xiuli (Frontiers in Cell and Developmental Biology, 2022)
As a major component of the enteroendocrine system, enterochromaffin (EC) cells play a key role in ulcerative colitis (UC). However, the scarcity of EC cells has limited the investigation of their function. In this study, we applied digital spatial profiling to acquire transcriptomic data for EC cells and other epithelial cells from colonoscopic biopsy samples from 8 UC patients and 7 healthy controls. Differential expression analysis, gene set enrichment analysis, and weighted gene co-expression network analysis were performed to identify differentially expressed genes and pathways and co-expression networks. Results were validated using an online dataset obtained by single-cell RNA sequencing, along with immunofluorescence staining and qRT-PCR. In healthy participants, 10 genes were significantly enriched in EC cells, functionally concentrated in protein and bioamine synthesis. A co-expression network containing 17 hub genes, including TPH1, CHGA, and GCLC, was identified in EC cells. In UC patients, EC cells gained increased capacity for protein synthesis, along with novel immunological functions such as antigen processing and presentation, whereas chemical sensation was down-regulated. The specific expression of CHGB and RGS2 in EC cells was confirmed by immunofluorescence staining. Our results illuminate the transcriptional signatures of EC cells in the human colon. EC cells’ newly observed functional shift from sensation to secretion and immunity indicate their pivotal role in UC.